The characterization and thermo-physical property investigations of SiO2/HFE7000 nanorefrigerants - M. R. M., Nawi; M. Z. A., Rehim; Azmi, W. H.; S. A., Razak (Elsevier, 2018)
This paper presents the characterizations and thermo-physical properties investigation of SiO2/HFE7000 nanorefrigerants for 0.005–0.02% volume concentrations and temperature ranges of 283–303 K. SiO2 nanoparticles were dispersed in HFE7000 refrigerants by utilizing the two-step method. The measurements of thermal conductivity and dynamic viscosity were performed by using KD2 Pro Thermal Properties Analyzer and LVDV-III Rheometer, respectively. The SiO2/HFE7000 nanorefrigerants shows high stability with the SiO2 nanoparticles remains suspended when observed for more than 90 days. The thermal conductivity is found increases by concentrations, but decreases by temperature. The highest thermal conductivity enhancement of 27% is observed at 0.02% volume concentration. Meanwhile, the dynamic viscosity of SiO2/HFE7000 nanorefrigerants increases by volume concentrations however decreases by temperatures. The nanorefrigerants behaved as Newtonian fluids. As a conclusion, the present novel SiO2/HFE7000 nanorefrigerants have potential in various heat transfer applications with great stability and thermo-physical properties behaviours.